Belongingness in early secondary school: Key factors that primary and secondary schools need to consider - Vaz, Sharmila; Falkmer, Marita; Ciccarelli, Marina; Passmore, Anne; Parsons, Richard; Black, Melissa; Cuomo, Belinda; Tan, Tele; Falkmer, Torbjorn (PUBLIC LIBRARY SCIENCE, 2015)
© 2015 Vaz et al. It is unknown if, and how, students redefine their sense of school belongingness after negotiating the transition to secondary school. The current study used longitudinal data from 266 students with, and without, disabilities who negotiated the transition from 52 primary schools to 152 secondary schools. The study presents the 13 most significant personal student and contextual factors associated with belongingness in the first year of secondary school. Student perception of school belongingness was found to be stable across the transition. No variability in school belongingness due to gender, disability or household-socio-economic status (SES) was noted. Primary school belongingness accounted for 22% of the variability in secondary school belongingness. Several personal student factors (competence, coping skills) and school factors (low-level classroom task-goal orientation), which influenced belongingness in primary school, continued to influence belongingness in secondary school. In secondary school, effort-goal orientation of the student and perception of their school's tolerance to disability were each associated with perception of school belongingness. Family factors did not influence belongingness in secondary school. Findings of the current study highlight the need for primary schools to foster belongingness among their students at an early age, and transfer students' belongingness profiles as part of the handover documentation. Most of the factors that influenced school belongingness before and after the transition to secondary are amenable to change.